Bioavailability of dissolved and crushed single tablets of bictegravir, emtricitabine, tenofovir alafenamide in healthy adults: the SOLUBIC randomized crossover study. (2nd November 2022) - Hocqueloux, Laurent; Lefeuvre, Sandrine; Bois, Julie; Brucato, Sylvie; Alix, Antoine; Valentin, Cécile; Peyro-Saint-Paul, Laure; Got, Laurence; Fournel, François; Dargere, Sylvie; Prazuck, Thierry; Fournier, Anna; et al.
Abstract: Background: Crushing or dissolving bictegravir/tenofovir alafenamide/emtricitabine (BIC/TAF/FTC) tablets is not recommended because there are no data supporting this practice. Methods: A crossover, randomized trial in healthy adults (NCT04244448) investigated the bioavailability of two off-label uses of BIC/TAF/FTC (50/200/25 mg), dissolved in water or crushed in apple compote, compared with the solid tablet. Pharmacokinetic (PK) parameters were estimated from sequential intensive plasma antiretroviral concentrations over a 72 h period post dose. Bioequivalence was met if the 90% CIs of the geometric least-squares means ratios comparing BIC/TAF/FTC exposures (AUC and C max ) from the experimental phases were within 80%–125% of the reference. Results: Eighteen subjects participated in each of the three phases. Dissolved tablet C max geometric mean ratio (90% CI) for BIC/TAF/FTC was 105% (93–119)/97% (87–108)/96% (74–124), respectively. Dissolved tablet AUC geometric mean ratio (90% CI) for BIC/TAF/FTC was 111% (100–122)/100% (94 to 105)/99% (81 to 120), respectively. Crushed tablet Cmax geometric mean ratio (90%) CI for BIC/TAF/FTC was 110% (97 to 124)/70% (63–78)/66% (51–85), respectively. Crushed tablet AUC geometric mean ratio (90%) CI for BIC/TAF/FTC was 107% (96–118)/86% (82–91)/84% (69–103), respectively. Conclusions: Crushing BIC/TAF/FTC tablets may lead to suboptimal emtricitabine and tenofovir alafenamide drug exposures. Dissolving BIC/TAF/FTC in water may be acceptable if the tablet cannot be swallowed whole.